Water and ice cloud optical thickness changes and radiative effects in East Asia. (October 2020) - Zhang, Hua; Zhao, Min; Chen, Qi; Wang, Qiuyan; Zhao, Shuyun; Zhou, Xixun; Peng, Jie
Highlights: We find there indeed existed long-term change trends of COT for both water and ice clouds in some sub-regions over East Asia. It is the first time to quantify both water and ice COT and their change effects on local radiative budget with satellite observational dataset in detail. The major contribution from liquid/ice cloud path and cloud effective radius changes to the COT changes are discussed too. Abstract: The climatologic mean and changes in cloud optical thickness (COT) of water and ice clouds in East Asia and their influence on the local radiation budget are studied quantitatively by using the Beijing Climate Center Radiative Transfer Model of BCC_RAD combined with satellite observational datasets from March 2000 to February 2018. Our results show that the annual mean COT over East Asia decreases from the southeast to the northwest, and the annual mean COT of water (COTw ) and ice cloud (COTi ) in this region are 15.0 and 11.6, respectively. The anomaly variations of COT illustrate that the variation intensity of COTw is stronger than that of COTi . Moreover, COT varies with sub-regions and seasons in East Asia. The trends of COTw in the northeastern and southern China are found to be 0.022 yr -1 and -0.071 yr -1, respectively, while the COTi trends over the two regions are 0.062 yr -1 and -0.009 yr -1, respectively. The annual mean shortwave-, longwave-, and net-radiative effects for the 18 years caused by water clouds in East Asia at the top-of-atmosphere (TOA)/surface are -72.4/-97.9, 15.7/31.1, and -56.7/-66.7 W m -2, respectively. The corresponding effect caused by ice clouds are -88.5/-107.5, 55.7/12.2, and -32.7/-95.3 W m -2, respectively. The shortwave cloud radiative effects (CREs) dominate the longwave CREs not only at the TOA but also at the surface, and the effects of COTi changes on the radiative budgets are stronger than those of COTw over the East Asia region.